KEMAMPUAN MENULIS TEKS NARASI DENGAN METODE MIND MAPPING PADA SISWA KELAS XI SMK NEGERI 8 KUPANG - Arwadi Talan; Karus M. Margareta; Dian Sari A. Pekuwali (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
This research focuses on the narrative writing ability of eleventh-grade students at SMK Negeri 8 Kupang using the mind mapping method. The purpose of this study is to describe students’ ability in writing narrative texts by paying attention to the structure and linguistic features of narrative texts. The theory applied in this research is writing theory, as the aspects analyzed relate to students’ ability to develop ideas, organize story plots, and use appropriate linguistic elements through their written work. The research method used is descriptive qualitative. This study was conducted on 26 students of class XI TJKT 3 at SMK Negeri 8 Kupang. The data were collected through a performance test in the form of a narrative writing task based on mind mapping created by the students. Data analysis focused on the narrative text structure, including orientation, complication, and resolution, as well as linguistic features such as the use of action verbs, mental verbs, time and place adverbs, chronological conjunctions, point of view, and cohesion and coherence. The results show that the narrative writing ability of students is categorized as fairly good, with an average score of 77.56. A total of 16 students or 61.54% achieved mastery, while 10 students or 38.46% did not meet the minimum mastery criteria. Based on these findings, it can be concluded that the narrative writing ability of eleventh-grade students at SMK Negeri 8 Kupang using mind mapping is generally fairly good, although several aspects still need improvement.